A Novel Zn (II)‐Based Metal‐Organic Framework as a Highly Selective and Sensitive Luminescent Sensor for the Detection of Nitrofuran Antibiotics. Issue 9 (24th January 2022) - Lu, Mengting; Xiao, Xiaoyan; Yu, Shijiang; Lin, Wenxin; Yang, Yu
Abstract: The abuse of antibiotics has led to serious environmental and health problems in the modern society. The detection on antibiotics with high selectivity and sensitivity is urgently needed. In this work, we synthesized a new zinc‐based metal‐organic frameworks, [Zn3 (TCPPDA)4 ] ⋅ 8DMF ⋅ 2H2 On, namely ZJU‐126. The as‐obtained ZJU‐126 has demonstrated its usage as a platform of luminescent sensor for nitrofurazone (NZF) and nitrofurantoin (NFT) with strong quenching constants and low detection limits of 5.8×10 4 M −1 and 0.56 μM for NZF as well as 4×10 4 M −1 and 0.82 μM for NFT, respectively. Particularly, ZJU‐126 exhibits excellent selectivity, anti‐interference and recyclability. The possible mechanism involved has also been discussed. Abstract :